Development of E-Learning PAI And Budi Pekerti Based on Higher Order Thinking Skills (HOTS) to Increase Learning Motivation and Learning Achievement Assessment in Senior High Schools in The City of Salatiga - Taufik, Bekti; Fatah Syukur; Ismail SM (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Specifically, from the development of PAI and Budi Pekerti learning materials, with application specifications in the form of a web display that is synchronized with the application on the android menu include: teacher name, student name, PAI material classes X, XI, and XII, video PAI learning according to each of the chapters discussed, questions, system of evaluation of higher order thinking skills consisting of the domain of cognitive, affective and psychomotor evaluation, username and password given to teachers and students, then after PAI training treatment, then the e-learning can be validated on the part of materials, learning media and applications by the experts. This research method uses research and development (R&D) with the thiagarajan model, known as the 4-D model that is carried out through 4 stages, namely definition, design, development, and dissemination. (disseminate). The results of this study show that: 1) E-learning needs analysis of PAI and Budi Pekerti based HOTS Assessment will focus on the development of content, evaluation, and evaluation using high-level thinking skills to drive and improve student learning performance; 2) One important component in building PAI e-Learning platforms is the use of PHP boostraps, hosting, and domains for PAI learning. This allows for adding materials to PAI & Budipekerti e-learning sites that match themes and lesson materials; 3) the goal of achieving highly dignified product quality is used through e -learning pai and high-thinking skills (HOTS) development through group focus discussions (FGD) and product evaluation. The result of the responses of validators from the fields of IT, media, learning materials, PAI evaluation evaluations, and staff, as well as student responses that show that such applications are highly worthy to be used; 4) Development of Biji-Puri eLearning products based on effective learning performance and HOTS employees can provide students with effective learning motivation and motivation.